2008
DOI: 10.1016/j.molcatb.2007.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Production of glycidyl ethers by chemo-enzymatic epoxidation of allyl ethers

Abstract: Production of glycidyl ethers is industrially carried out by reacting alcohols with epichlorhydrin, a potentially carcinogenic compound. This paper investigates a less hazardous alternative -that of a chemo-enzymatic process in which Candida antarctica lipase B catalysed generation of peracid from a carboxylic acid is followed by a Prileshajev epoxidation of the corresponding allyl ether.Trimethylolpropane monoallyl ether (TMPME) was used as a model substrate. A maximal epoxide product yield of 77% was achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…6b, increasing levels of OA increase the initial reaction rate in a low concentration range, while the reaction rate drops at high OA concentrations. It might also be due to the ring-opening tendency of carboxylic acids which is a major cause for low yields in epoxide production processes [13,22]. It might also be due to the ring-opening tendency of carboxylic acids which is a major cause for low yields in epoxide production processes [13,22].…”
Section: Influence Of Octanoic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…6b, increasing levels of OA increase the initial reaction rate in a low concentration range, while the reaction rate drops at high OA concentrations. It might also be due to the ring-opening tendency of carboxylic acids which is a major cause for low yields in epoxide production processes [13,22]. It might also be due to the ring-opening tendency of carboxylic acids which is a major cause for low yields in epoxide production processes [13,22].…”
Section: Influence Of Octanoic Acidmentioning
confidence: 99%
“…1) using silcoat-NZ435 as the biocatalyst, H 2 O 2 as the oxidant, and octanoic acid (OA) as the acyl donor was investigated. The choice of 1-dodecene as a model educt was influenced by the fact that terminal alkene epoxides are known to be among the industrially most important epoxides [12], while terminal alkenes themselves are among the most difficult to epoxidize [13]. The choice of 1-dodecene as a model educt was influenced by the fact that terminal alkene epoxides are known to be among the industrially most important epoxides [12], while terminal alkenes themselves are among the most difficult to epoxidize [13].…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene glycol allyl glycidyl ether (PGAGE) and the allyl polyoxyethylene ether (APEG), tethering with both alkene and epoxy groups, are widely used as fabric finishing agent [1][2] , reactive diluent [3] , cross-linking agent, chemical fixation of carbon dioxide [4][5], and nonionic surfactants for detergents. [6] In addition, the PGAGE and APEG are often used to improve the properties such as viscosity of the epoxy resins.…”
Section: Introductionmentioning
confidence: 99%
“…More polar solvents, which should increase the partitioning of H 2 O 2 to the organic phase, have not been thoroughly investigated. Use of ethyl acetate has been reported,16 but this is not only a solvent but also a substrate for the enzyme, resulting in formation of peracetic acid that has an inactivating effect on the enzyme 17. Furthermore it has been reported that hydrophilic solvents can form hydrogen bonds with the peracid and hence slow down the epoxidation step of the reaction 18…”
Section: Introductionmentioning
confidence: 99%